The Efficacy and Safety of Holmium Laser Enucleation of Prostate Compared With Bipolar Technologies in Treating Benign Prostatic Hyperplasia: A Systematic Review and Meta-Analysis of 10 Randomized Controlled Trials. Issue 6 (December 2022) - Che, Xuanyan; Zhou, Zhongbao; Chai, Yumeng; Cui, Yuanshan; Zhang, Yong
We performed a systematic review and meta-analysis on efficacy and safety of holmium laser enucleation of prostate compared with bipolar technologies in treating benign prostatic hyperplasia. We analyzed several databases such PubMed, Embase, and Web of Science. Two reviewers independently reviewed studies for consistent criteria and extracted relevant data. Reviewers independently assessed the risk of bias and strength of the evidence for the body of the literature. Ten randomized controlled trials including 1, 157 participants were included in this meta-analysis. The holmium laser group had favorable perioperative outcomes in this study. The holmium laser group identified shorter catheterization duration and shorter hospital stay duration than the bipolar technologies group. Efficiency outcomes, such as International Prostate Symptom Score, peak urinary flow rate, quality of life, postvoid residual urine volume, and international index of erectile function reported no obvious differences between the holmium laser and bipolar technologies groups at the 6 to 12 months follow-up. Bipolar technologies and holmium laser groups shared equivalent effectiveness and safety in treatments for benign prostate hyperplasia. Holmium lasers identified lower catheter times, shorter hospital stays, and lesser risk of hemorrhage than bipolar technologies.